The role of vitamin D in periodontal health and disease - Lu, Emily Ming‐Chieh (Journal of periodontal research, 2023)
Vitamin D plays an essential role in calcium and bone metabolism, immune regulation and possesses profound anti‐inflammatory effects. Evidence suggests that low serum vitamin D is associated with increased severity of periodontitis, a chronic inflammatory condition characterised by destruction of the supporting tissues surrounding the tooth, which has several shared risk factors with other chronic non‐communicable diseases. The biological functions of vitamin D are mediated by its strong anti‐microbial, anti‐inflammatory, and host modulatory properties. Experimental periodontitis models involving targeted deletion of 1α‐hydroxylase, the enzyme responsible for the conversion of inactive substrate to active 1,25(OH)2D3 (calcitriol), showed augmented alveolar bone loss and gingival inflammation. Vitamin D receptor (VDR) gene polymorphisms have also been associated with increased severity of periodontitis. Thus, the involvement of vitamin D in the pathogenesis of periodontitis is biological plausible. Clinical studies have consistently demonstrated an inverse relationship between serum 25OHD3 and periodontal disease inflammation. However, due to the paucity of well‐designed longitudinal studies, there is less support for the impact of vitamin D status on periodontal disease progression and tooth loss. The evidence emphasises the importance of maintaining vitamin D sufficiency in supporting periodontal health. This review aims to first examine the biological mechanisms by which vitamin D might influence the pathogenesis of periodontal disease and second, discuss the clinical evidence which implicate the role of vitamin D in periodontal disease.